Strategi Dinas Sosial Dalam Penanganan Gelandangan Penderita Psikotik Di Lingkungan Pondok Sosial (Liponsos) Keputih Surabaya - Nira Zhafirah Puspitasari; Ertien Rining Nawangsari (Universitas Mataram, 2022)
The city of Surabaya is the center of the largest population of people with severe mental disorders (ODGJ) in East Java Province and continues to increase until 2020 to as many as 5519 people. ODGJ are one of the groups that are vulnerable to being neglected and become victims of neglect for various reasons such as social factors, economic factors, health factors, and others. The Surabaya City Government through the Surabaya City Social Service in this case has taken steps to deal with these problems, one of which is by building the Keputih Regional Environmental Technical Implementation Unit (UPTD Liponsos). The research method used is qualitative research and uses data collection techniques through observation, interviews, and documentation. The results and conclusions of this study indicate that: 1) Strategy formulation uses communication and coordination with stakeholders. 2) Strategy implementation is carried out in 4 ways: social rehabilitation, social empowerment, social protection, and social security. Furthermore, socialization was carried out in the workforce in terms of capacity building for knowledge transfer and also conducting rotations or tours of duty. 3) Strategy evaluation is carried out by monitoring in a structured and good manner by making a priority scale and coordinating with regional apparatus organizations (OPD).